2006 European Conference on Wireless Technologies 2006
DOI: 10.1109/ecwt.2006.280435
|View full text |Cite
|
Sign up to set email alerts
|

Tilting and Beam-shaping for Traffic Load Balancing in WCDMA Network

Abstract: This paper' summarizes recent developments in semi-smart antenna systems for geographic load balancing in cellular mobile communication systems by cooperatively changing the antenna radiation patterns and compares the performance with cooperatively down tilted antennas. Cooperative coverage is advantageous, e.g. in the presence of hotspots. For semi-smart antennas the ideal shape for a cell in the context of its neighbours is determined using the Bubble Oscillation Algorithm (BOA) and the pattern is then given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The application of smart antennas in wireless network has also been widely investigated. However most work related to traffic load balancing only focuses on different radio channel allocation schemes and most work on smart antennas [1] only consider the radio propagation channels within one cell. These severely limit their efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of smart antennas in wireless network has also been widely investigated. However most work related to traffic load balancing only focuses on different radio channel allocation schemes and most work on smart antennas [1] only consider the radio propagation channels within one cell. These severely limit their efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It can be used to improve performance for any distributed system containing nonuniformly distributed traffic, especially for resolving the traffic hot spots. Studies on dynamic sectorisation, use of tilted antennas [1] and dynamic cell size control (cell breathing) [2] [4] have shown that the system performance can be improved by balancing non-uniformly distributed load. Increasingly, web services are provided by massive, geographically diverse "Internet-scale" distributed systems, some having several data centers each with hundreds of thousands of servers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in [8][9][10], optimum tilting was treated in view of the BS antenna characteristics, the cells sectorization, the site spacing, the number of signal paths, and the traffic volume showing that optimum tilting depends on various network parameters. Finally, in [11], an adaptive tilting method was proposed for interference mitigation and capacity enhancement in WCDMA systems, revealing the importance of beam tilting in wireless communications.…”
Section: Introductionmentioning
confidence: 99%
“…Authors in [74] compare the impact of cooperative beam shaping with the cooperative tilt adaptation for LB. The tilt based approach has relatively less margin for performance improvement but it is more pragmatic as it is implementable with conventional widely commercialised parabolic…”
Section: A) Load Balancing Via Antenna Adaptationmentioning
confidence: 99%